2018
DOI: 10.1371/journal.pone.0199687
|View full text |Cite
|
Sign up to set email alerts
|

Using mHealth to improve tuberculosis case identification and treatment initiation in South Africa: Results from a pilot study

Abstract: BackgroundTuberculosis (TB) incidence in South Africa is among the highest globally. Initial loss to follow-up (ILFU), defined as not starting on TB treatment within 28 days of testing positive, is undermining control efforts. We assessed the feasibility, acceptability, and potential of a mHealth application to reduce ILFU.MethodsAn mHealth application was developed to capture patients TB investigation data, provide results and monitor treatment initiation. This was implemented in two primary health clinics (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Reducing or eliminating the patient-level complexity and duration of evaluation for TB and other OIs may improve LTC [52]. Rapid near POC testing with Xpert MTB/RIF [53], POC testing with TB-LAM [54], co-locating TB and HIV diagnostic and treatment services [55], and telephonic delivery of test results to providers and patients (before or after ART initiation) have all shown promise for streamlining TB and HIV care integration [56].…”
Section: A New Approach To Framing Linkage To Carementioning
confidence: 99%
“…Reducing or eliminating the patient-level complexity and duration of evaluation for TB and other OIs may improve LTC [52]. Rapid near POC testing with Xpert MTB/RIF [53], POC testing with TB-LAM [54], co-locating TB and HIV diagnostic and treatment services [55], and telephonic delivery of test results to providers and patients (before or after ART initiation) have all shown promise for streamlining TB and HIV care integration [56].…”
Section: A New Approach To Framing Linkage To Carementioning
confidence: 99%
“…Given the wide coverage of mobile phone networks, mHealth holds promise as an important delivery tool for healthcare delivery in resource-constrained regions (figure 1). mHealth interventions are in use for diagnosis and management of various infectious diseases including malaria,39 tuberculosis40 and human immunodeficiency virus (HIV)41 and for improving maternal and fetal health42 in several developing countries. Although mHealth interventions are increasingly used for non-communicable diseases,43–45 some studies highlight only a modest impact in non-communicable disease (NCD) control, likely due to limited number of studies and impact on process of care alone 46 47.…”
Section: Discussionmentioning
confidence: 99%
“…Security and privacy issues have been well documented in South Africa, especially for mHealth platforms [ 22 , 41 , 42 ]. However, previous studies have shown that personal identification number (PIN)–protected mobile platforms for delivering sensitive health information are feasible and acceptable in South Africa [ 42 , 43 ]. Furthermore, a Japanese study that investigated online consumption suggests that the process of making online purchases for the first time during the lockdown has facilitated people becoming familiar with technology, thus alleviating some perceived barriers [ 44 ].…”
Section: Discussionmentioning
confidence: 99%